The Leon Lewille memorial lecture: Biomechanics and Medicine in Swimming, past, present and future - Vilas-Boas, J. P. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: The aim of this paper was to analyse the ten Biomechanics and Medicine in Swimming (BMS) books available, in order to characterize the past and the actual state of the art on Biomechanics and Medicine in Swimming research, and try to find support to speculate about the future trends of development. METHODS: The first ten books of the BMS series were analysed, characterizing their contents and authorship, and relating the output with the general body of knowledge in swimming science. The approach was tried in four steps: (i) number of papers published; (ii) affiliation of the first author; (iii) number of papers per category of analysis, and (iv) scientific content. The categories of analysis were defined based on Clarys (1996) Foreword to BMS VII. The analysis was performed considering the researcher`s personal classification of each paper, considering, by order: (i) title; (ii) key-words; (iii) editorial classification, and (iv) content of the article. A total of 622 papers were analysed. To allow further analysis of the findings, and trying to characterize more globally the swimming science peer reviewed and indexed research tendencies, a PubMedTM search was conducted (15th January 2010). RESULTS: A progressive tendency for a growing number of papers was perceived, particularly in the last 3 volumes. In these books, an increased number of participant countries was also noted, but not proportional to the increased number of papers. A total of 41 countries entered in the BMS series as affiliation countries of the first authors. Japan and USA are the highest contributors. A tendency to the following hierarchy of the three prevalent research domains was observed: (i) Biomechanics; (ii) Physiology, and (iii) Evaluation. It is also possible to perceive a tendency for the preservation of this hierarchy along the BMS series (book to book analysis). From PubMedTM, a slightly different hierarchy of research domains was extracted. A tendency was noted for a higher importance of "Physiology" and "Medicine", and reduced expression of "Biomechanics", inclusively compared with "Training", for instance. DISCUSSION: In order to further explore the results obtained, a deeper critical analysis of the contents of each one of the ten BMS books was conducted. The perceived trends were used to allow foundations for some speculations about the expected future achievements on the domain of Biomechanics and Medicine in Swimming.